The impact of DFIG and FSIG wind farms on the small signal stability of a power system - Fayek, H.M. (IEEE Computer Society, 2014)
This paper investigates the impact of integrating a wind farm on the small signal stability of a two-area multi-machine power system. Two types of wind turbine generators were considered and compared against each other, namely the Doubly-Fed Induction Generator (DFIG) and the Fixed-Speed Induction Generator (FSIG). Multiple schemes and system configurations were studied through eigenvalue analysis and nonlinear time domain simulations. Results demonstrate that wind farms generally had a positive impact on the damping of the undesired electro-mechanical oscillations and overall system stability; however, such positive impact was not achieved in all scenarios. Â© 2014 IEEE.